2021
DOI: 10.1186/s12933-021-01272-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium‐glucose cotransporter type 2 inhibitors on cardiovascular, renal, and safety outcomes in patients with cardiovascular disease: a meta‐analysis of randomized controlled trials

Abstract: Background Controlled studies and observational studies have shown that sodium-glucose cotransporter type 2 inhibitors (SGLT-2i) are beneficial for the survival of patients with heart failure (HF). However, it is unclear whether SGLT-2i can provide benefit in patients with other cardiovascular diseases. Here, we conducted a systematic review and meta-analysis to determine the outcomes of cardiovascular, renal, and safety outcomes of SGLT-2i administration in patients with cardiovascular disease… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 62 publications
0
14
0
1
Order By: Relevance
“…Other studies specifically focused on populations with T2D and CKD or HFrEF [ 8 , 9 , 14 ]. They generally found that compared with placebo SGLT2i protect the kidney and reduce the incidence of hHF [ 2 4 , 6 , 8 10 , 12 14 , 28 , 29 ]. However, due to the relatively high baseline risk of the participants in these trials, external validity to the general T2D population has been questioned [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies specifically focused on populations with T2D and CKD or HFrEF [ 8 , 9 , 14 ]. They generally found that compared with placebo SGLT2i protect the kidney and reduce the incidence of hHF [ 2 4 , 6 , 8 10 , 12 14 , 28 , 29 ]. However, due to the relatively high baseline risk of the participants in these trials, external validity to the general T2D population has been questioned [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such trends were observed in other CVOTs and other real-world evidence (RWE) [ 2 4 , 6 , 34 ]. Of note, in these reports SGLT2i reduce hHF episodes more overtly relative to ACM [ 6 , 28 ]. Here, however, in the low baseline kidney risk categories ACM incidence was consistently lower in SGLT2i initiators, while the risk for hHF was not stable, i.e., significant between group differences were observed only in the eGFR > 90 ml/min/1.73 m 2 category.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the relative effectiveness of each product on the different outcomes remains to be elucidated, because study populations and designs are different. Recent attempts to indirectly address this issue through network meta-analyses led to differing conclusions regarding the differential effect of individual SGLT2i on outcomes such as HF and all-cause mortality [ 44 , 45 ]. Therefore, in the absence of prospective or retrospective head-to-head trials comparing individual SGLT2i, it cannot be ascertained to what extent the exposure to the individual SGLT2i in CVD-REAL Catalonia vs. other studies could have contributed to the observed differences.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, some GLP-1RAs protect from MACE (usually composed of cardiovascular death or nonfatal stroke or myocardial infarction) 21,23,25,26,30 and SGLT2 inhibitors reduce hHF and improve kidney outcomes. 9,[13][14][15][16][17][18][19][27][28][29]36 Some evidence indicates that specific SGLT2 inhibitors also reduce MACE rate 9,14,37 and GLP-1RAs reduce proteinuria and may improve kidney outcomes in T2D. 22,24,[38][39][40] GLP-1RAs were also shown to increase the likelihood of nonalcoholic steatohepatitis resolution.…”
mentioning
confidence: 99%